HUBUNGAN MEDIA KOMUNIKASI K3 DENGAN PENGETAHUAN DAN SIKAP PENGGUNAAN ALAT PELINDUNG DIRI PADA KARYAWAN BAGIAN PRODUKSI - Lusha Ayu Astari (Sekolah Ilmu Kesehatan Dan Ilmu Alam (SIKIA), Universitas Airlangga, 2019)
One of the prevention of workplace accidents is to use a personal protective equipment (PPE), but there are still many workers who do not want to use it for various reasons. OHS communication media is one way to improved knowledge and attitudes of workers used PPE. The purpose of this study was to know the relationship between the number of OHS communication media that respondents received with the knowledge and attitude of the PPE. The study design was cross-sectional. Determination of the number of respondents used total sampling methods and get 48 respondents. Data collected by interview used a questionnaire and observation with the checklist that refers to the Workplace Safety and Health for Industrial Marine. The result of knowledge level about PPE of 88% of respondents has been good and 65% of respondents had a positive attitude to the use of PPE. OHS media communication that given by company include in enough category (73%) and the result of analysis OHS communication media with knowledge about PPE used contingency coefficient has a value of 0.412, while analysis OHS communication media with the attitude factor has a value 0,204. In conclusion, the number of OHS communications media received by employees with the level of knowledge have a moderate relationship and the number of OHS communication media received by employees with the attitude of the PPE have a weak relationship.